Serum Cytokine Levels are related to Nesfatin-1/NUCB2 Expression in the Implantation Sites of Spontaneous Abortion Model of CBA/j × DBA/2 Mice - Chung, Yiwa (Dev Reprod, 2017)
The process of spontaneous abortion involves a complex mechanism with various cytokines, growth factors, and hormones during the pregnancy. However, the mechanism underlying spontaneous abortion by pro- and anti-inflammatory cytokines in the serum during the pregnancy is not fully understood. Therefore, the purpose of this study was to examine the relationship between the serum levels of pro- and anti-inflammatory cytokines and spontaneous abortion using the CBA/j × DBA/2 mouse model. Serum levels of pro-inflammatory cytokines, such as IFN-γ, IL-1α and TNF-α were not increased in abortion model mice, but anti-inflammatory cytokines, such as IL-4, IL-13 and IL-1ra were decreased compared to normal pregnant mice. In addition, serum levels of chemokine, such as SDF-1, G-CSF, M-CSF, IL-16, KC and MCP-1 were decreased in abortion model mice compared to normal pregnant mice. However, the expression levels of nesfatin-1/NUCB2 mRNA and protein in the uteri of implantation sites were significantly higher in abortion model mice than normal pregnant mice. These results suggest that uterine nesfatin-1/NUCB2 expression may be down-regulated by inflammatory cytokines and chemokines in the serum of pregnant mice. Moreover, this study suggests the possibility that nesfatin-1/NUCB2 expressed in the implantation sites may be associated with the maintenance of pregnancy.